Sea Ice Prediction Network-South: coordinating seasonal predictions of sea ice for the Southern Ocean [in 'State of the Climate in 2019'] - Jan Lieser; Massonnet, F; William Hobbs; Fyfe, J; Bitz, CM; Phillip Reid (2020)
The Sea Ice Prediction Network (SIPN) is a community-wide effort to assess seasonal sea ice forecasts for the Arctic. It has been in operation since 2008, when it started life as the SEARCH Sea Ice Outlook (Hamilton and Stroeve 2016). This international initiative has created a strong community of researchers from various backgrounds with a common interest in forecasting sea ice conditions in the Arctic Ocean.